Differentiation of Bicep femoris and Semimembranosus muscles of smoked dry-cured ham by quality parameters - Marušić, Nives, inženjerka prehrambene tehnologije; Mikulić, Ana, prehrambena inženjerka; Turk, Martina; Medić, Helga (2019)
The aim of this work was to determine the effect of fat and protein oxidation on the colour and texture of Biceps femoris (BF) and Semimembranosus (SM) muscles of smoked dry-cured ham Dalmatinski pršut. Fat and protein oxidation was determined by spectrophotometer methods of which fat oxidation by 2-thiobarbituric acid reactive substances method (TBARS) and protein oxidation by 2,4-dinitrophenylhydrazine (DNPH) method. Colour parameters (L*a*b* values) and texture profile analysis (TPA test) were also analysed. There was no statistical significant difference (P>0.05) between BF and SM in fat and protein oxidation. SM is an external muscle and is more exposed to oxygen than internal muscle BF. As a result of that SM showed slightly higher TBARS values than BF. Slightly higher values of carbonyls in BF can be explained by the higher water content in this internal muscle and thus by the stronger proteolytic activity. BF had higher L*, a* and b* values than SM. Higher values of adhesive force, cohesiveness and stringiness and lower values of hardness, adhesiveness, gumminess, chewiness and fracture were found for BF than for SM.
Bibliografija: str. 8-9.
Abstract.
Keywords: Suhomesnati proizvodi -- Dimljeni pršut -- Karbonili -- Tekstura -- Boja -- Oksidacija masnih kiselina